Um estudo sobre o caso José Rodrigues versus the S. Paulo Tramway, Light and Power - Beserra, Matheus Eduardo (Universidade Federal Rural do Semi-Árido, 2019)
The current work has as its object of study a reconstruction of the institutional history of the National Labor Council (CNT) using the case nº 4.391 of 1934 as a tool to reflect about the object during the period in which the case ocurred. The case refers to José Rodrigues versus The São Paulo Tramway, Light and Power regarding a labor claim. The study proposes a deep examination of the case as well as the use of capable authors to assist in the interpretation of the collected data. Therefore, an inductive method was used and, based on the information found, it was possible to conclude that, although being an organ responsible to observe the application of labour laws, the CNT not always acted that way, such as in this case, where it was coopted by the conjucture of its time, causing an overlap of politics over law.
Monografia
Keywords: CNT; Regulação trabalhista; Justiça do trabalho; Estado de exceção; CNT; Labor laws; Labor courts; State of exception; CIENCIAS SOCIAIS APLICADAS::DIREITO